Exploring robotics with Robotis systems - Thai, Chi N. (Springer, 2015)
This book presents foundational robotics concepts using the ROBOTIS BIOLOID and OpenCM-904 robotic systems, and is suitable as a curriculum for a first course in robotics for undergraduate students or a self-learner. It covers wheel-based robots, as well as walking robots. Although it uses the standard “Sense, Think, Act” approach, communications (bot-to-bot and PC-to-bot) programming concepts are treated in more depth (wired and wireless ZigBee/BlueTooth)